2022
DOI: 10.1007/s00784-022-04652-1
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy and 3% potassium nitrate gel as treatment of cervical dentin hypersensitivity: a randomized clinical trial

Abstract: Objectives This randomized controlled trial aimed to evaluate different protocols for dentin hypersensitivity treatment with low-power lasers and desensitizing agents, and the association between low-power lasers and desensitizing agents. Materials and methods Fifty-four patients (303 teeth) were randomly allocated to three groups: G1, 3% nitrate potassium gel, UltraEZ ( n = 17); G2, photobiomodulation therapy (PBM) with a low-level infrared l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Os lasers de baixa potência atuam no potencial elétrico da membrana celular, ativando as bombas Na+/K+ ATPase, trazendo benefícios analgésicos e modulando os efeitos anti-inflamatórios do tecido. Diante disso, após três sessões de irradiação, observou-se redução da dor de 55,75%; após 3 meses, era de 64,30%, em concordância com a literatura (TOLENTINO et al 2022).…”
Section: Resultsunclassified
“…Os lasers de baixa potência atuam no potencial elétrico da membrana celular, ativando as bombas Na+/K+ ATPase, trazendo benefícios analgésicos e modulando os efeitos anti-inflamatórios do tecido. Diante disso, após três sessões de irradiação, observou-se redução da dor de 55,75%; após 3 meses, era de 64,30%, em concordância com a literatura (TOLENTINO et al 2022).…”
Section: Resultsunclassified
“…There are various clinical protocols that dental practitioners can follow. Most of the studies found that pain levels were significantly reduced 3 months after the therapies [106].…”
Section: Low-level Laser Therapymentioning
confidence: 99%
“…Recent studies have demonstrated that new types of DAs have comparable desensitizing effects on dentine. These include nano-hydroxyapatite (n-HAp) [ 21 , 22 , 23 ], photobiomodulation therapy (PBM) with a low-level infrared laser [ 24 ], nano-sized carbonate apatite (n-CAP) [ 25 ], zinc-containing desensitizer [ 26 ], etc. Most of the DAs block the opening of the bulk of the dentinal tubules and make the dentinal surface smooth by filling the irregularities, thereby decreasing the sensitivity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%